2010
DOI: 10.1097/brs.0b013e3181edea9c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intermittent Retraction on Paraspinal Muscle Function During Lumbar Surgery

Abstract: Although histologically there was a reduction in muscle damage in patients that underwent intermittent retraction, there was no benefit on clinical outcome. Paraspinal muscle shows evidence of reinnervation after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several previous studies have revealed the histological, histochemical and enzymatic adverse effects of lumbar muscle retraction after back surgery [30,31,32,33]. Muscle dissection itself, accompanied by additional retraction injuries, can lead to denervation of the muscles [34], as well as increased muscle pressure as a consequence of alterations in muscle blood flow [33,35]. Kawaguchi et al [31] reported that back muscle injuries were related to the retraction pressure and its time and extent of exposure, and marked edema and fiber necrosis were obvious and creatine phosphokinase activity tended to be high as the pressure/time of retraction increased.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have revealed the histological, histochemical and enzymatic adverse effects of lumbar muscle retraction after back surgery [30,31,32,33]. Muscle dissection itself, accompanied by additional retraction injuries, can lead to denervation of the muscles [34], as well as increased muscle pressure as a consequence of alterations in muscle blood flow [33,35]. Kawaguchi et al [31] reported that back muscle injuries were related to the retraction pressure and its time and extent of exposure, and marked edema and fiber necrosis were obvious and creatine phosphokinase activity tended to be high as the pressure/time of retraction increased.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative evaluation was not considered appropriate given the oedema of the paraspinal musculature and potential hyperesthesia at the level of the fracture. Evidence of reinnervation should be present at 6 months post-surgery, indicating a valid time point from when to evaluate patients [27]. Potential for rehabilitation has been shown not to change after this period [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…3,6 The postoperative muscle abnormalities are believed to be related to retraction of the muscles during surgery. [10][11][12][13][14][15][16] Abnormalities in muscle may also be identified using magnetic resonance imaging (MRI) techniques with resulting increased T2 signal intensity ratio of the affected muscle relative to control muscle on axial cross-sections. 9 This has been also shown in human subjects both histologically and by measurement of various serum markers for muscle injury and inflammation.…”
mentioning
confidence: 99%